Analisis Penjualan Produk Paket Kuota Internet Dengan Metode K-Nearest Neighbor - Handoko, Dedi; Tambunan, Heru Satria; Hardinata, Jaya Tata (STIKOM Tunas Bangsa Pematangsiantar, 2021)
PT. Akses Lintas Nusantara is a company engaged in the sale of Internet Quota Packages and package balances. This company has various data packages ranging from 6 GB, 11 GB, 21 GB and 32 GB with various price variations. Based on data on sales of internet quota package products for the past 1 (one) year, predictions for future sales are needed in order to facilitate the company in planning the provision of internet quota package stock. The K-Nearest Neighbor (KNN) algorithm is a method that is a supervised algorithm where the results of the new test sample are classified based on the majority of the categories on the KNN. To find out the sales of these products, the K-Nearest Neighbor algorithm is used. The expected result is to make it easier for companies to predict the future supply of internet quota packages in each region or region. The results of the research that have been carried out are prediction of Internet Quota Package Sales consisting of SP CL1, SPCL2, SPCL4 and SP CL8 with an Accuracy of 71.43%.